Lactobacillus fermentum CRL 722 is able to deliver active α-galactosidase activity in the small intestine of rats - Leblanc, Jean Guy Joseph (2005)
α-galactooligosaccharides (α-GOS) found in legumes such as soybeans can cause gastrointestinal disorders since mammals lack α-galactosidase (α-Gal) in the small intestine which is necessary for their hydrolysis. Lactobacillus fermentum CRL 722 is a lactic acid bacterium (LAB) capable of degrading α-GOS due to its elevated α-Gal activity. When conventional rats were fed live L. fermentum CRL 722 or cell-free extracts of this strain, a short-lived α-Gal activity was detected in the upper gastrointestinal tract. The safety of this LAB was also assessed. L. fermentum CRL 722 could thus be used as a vehicle to safely confer α-Gal in the small intestine of monogastric animal.